Effective debrief matters - Dick, F. (New Studies in Athletics, 2012)
In the context of an Olympic Games or major sports campaign, excellence is achieving or surpassing the intended performance "on the day." At best, this may mean a gold medal or a championship. At least, it must mean the best performance of the season. The debrief after the event focuses on why excellence was or was not achieved. It is the key to the review process and dictates the quality of lessons learned and consequently the changes to what is done and how it is done - redefining and taking ownership of excellence, designing the plan and then delivering objectives through effective action. For high-performance athletics programmes, the debriefing and the fouryear review and planning process should take place soon after the Olympic Games. The cheers that marked the athletes` last step on to the podium in London 2012 also marked the first step towards the podium in Rio 2016. The author, an experienced athletics head coach, provides a framework for debriefing and planning throughout the preparation cycle. Included are key questions for the short-, medium- and longterm reviews that can be used as guides for the process.